Teaching Strategy: Adaptive Mathematics Learning with Liveworksheets Platform - Sariningsih, Ratna; Kusuma, Jaka Wijaya; Linda, Linda (Universitas Muhammadiyah Mataram, 2025)
Technology is a supporting asset for the implementation of the teaching and learning process in educational institutions, and its application can be studied through research. This study uses a qualitative descriptive method with the aim of identifying the application of adaptive learning in mathematics learning with the help of Artificial Intelligence (AI) in the digitalization of mathematics education course. This study aims to identify the application of adaptive learning in mathematics instruction with the assistance of Artificial Intelligence (AI) in the course on the digitalization of mathematics education. The research was developed using the design thinking method (empathize, define, ideate, prototype, and test), resulting in a product consisting of teaching tools (media, assessments, and student worksheet) independently created by students of class B1 Mathematics Education at IKIP Siliwangi. The instruments used were validation sheets included in form applications and polls on the WhatsApp application. The validation and poll results were analyzed using real-time techniques with Apache Spark. The teaching tools in this study were validated by practitioners and tested on a group of students. Based on the practitioner’s validation and evaluations results, and student tests, the AI-assisted teaching tools for the digitalization of mathematics education course were deemed suitable for use and beneficial in the teaching and learning process.